Five years clinical outcomes after implantation of Absorb bioresorbable vascular scaffold pilot study in a single center with real world patients, with pre scaffold treatment and guided by intravascular imaging - Costantino Costantini; Sergio Tarbine; Costantino O. Costantini; Vinicius Shibata; Marcos Denk; Rafael Michel de Macedo (2022)
BackgroundThe safety and performance of the Absorb Vascular Scaffold (BVS) (Abbott Vascular, Santa Clara, CA) has been previously demonstrated with clinical data. However, these trials included patients with simple lesions. The Absorb III trial demonstrated an excess of adverse events following BVS implantation. Aiming to evaluate clinical outcomes, we analyzed the treatment of real-world patients in a pilot study from a single center, using optimal technique and intravascular image guidance in all cases, followed during 5 years.MethodsObservational retrospective pilot study in a single Brazilian center from 12/2014 to 10/2016, including 100 patients treated with BVS implantation. Safety and efficacy outcomes were analyzed in the in-hospital and late follow-up (5 years).ResultsMean age was 58.1 years; 88% were male, 31% had diabetes, and 28% presented with acute coronary syndromes. A total of 171 lesions in 141 vessels were treated with 190 BVS (mean 1.9 scaffolds/patient). Further intervention following intravascular imaging to optimize BVS implantation was required in 31% of patients. Procedure success was 100%. All patients completed a 5-year follow-up. The clinical events rate were: all-cause mortality 2%, cardiac death 0%, MI 2%, target vessel myocardial infarction 0%, TVR 16%, definite scaffold thrombosis 0%.ConclusionsIn this real-world experience, the use of intravascular imaging to guide BVS implantation was associated with a high 5-year event-free survival rate, with no scaffold thrombosis.DisclosuresCostantino R Costantini: Nothing to disclose. Sergio G Tarbine: Nothing to disclose. Costantino O Costantini: Nothing to disclose. Vinicius Shibata: Nothing to disclose. Marcos Denk: Nothing to disclose. Rafael Macedo: Nothing to disclose. BackgroundThe safety and performance of the Absorb Vascular Scaffold (BVS) (Abbott Vascular, Santa Clara, CA) has been previously demonstrated with clinical data. However, these trials included patients with simple lesions. The Absorb III trial demonstrated an excess of adverse events following BVS implantation. Aiming to evaluate clinical outcomes, we analyzed the treatment of real-world patients in a pilot study from a single center, using optimal technique and intravascular image guidance in all cases, followed during 5 years. The safety and performance of the Absorb Vascular Scaffold (BVS) (Abbott Vascular, Santa Clara, CA) has been previously demonstrated with clinical data. However, these trials included patients with simple lesions. The Absorb III trial demonstrated an excess of adverse events following BVS implantation. Aiming to evaluate clinical outcomes, we analyzed the treatment of real-world patients in a pilot study from a single center, using optimal technique and intravascular image guidance in all cases, followed during 5 years. MethodsObservational retrospective pilot study in a single Brazilian center from 12/2014 to 10/2016, including 100 patients treated with BVS implantation. Safety and efficacy outcomes were analyzed in the in-hospital and late follow-up (5 years). Observational retrospective pilot study in a single Brazilian center from 12/2014 to 10/2016, including 100 patients treated with BVS implantation. Safety and efficacy outcomes were analyzed in the in-hospital and late follow-up (5 years). ResultsMean age was 58.1 years; 88% were male, 31% had diabetes, and 28% presented with acute coronary syndromes. A total of 171 lesions in 141 vessels were treated with 190 BVS (mean 1.9 scaffolds/patient). Further intervention following intravascular imaging to optimize BVS implantation was required in 31% of patients. Procedure success was 100%. All patients completed a 5-year follow-up. The clinical events rate were: all-cause mortality 2%, cardiac death 0%, MI 2%, target vessel myocardial infarction 0%, TVR 16%, definite scaffold thrombosis 0%. Mean age was 58.1 years; 88% were male, 31% had diabetes, and 28% presented with acute coronary syndromes. A total of 171 lesions in 141 vessels were treated with 190 BVS (mean 1.9 scaffolds/patient). Further intervention following intravascular imaging to optimize BVS implantation was required in 31% of patients. Procedure success was 100%. All patients completed a 5-year follow-up. The clinical events rate were: all-cause mortality 2%, cardiac death 0%, MI 2%, target vessel myocardial infarction 0%, TVR 16%, definite scaffold thrombosis 0%. ConclusionsIn this real-world experience, the use of intravascular imaging to guide BVS implantation was associated with a high 5-year event-free survival rate, with no scaffold thrombosis. In this real-world experience, the use of intravascular imaging to guide BVS implantation was associated with a high 5-year event-free survival rate, with no scaffold thrombosis.